2020
DOI: 10.1038/s41467-019-13747-5
|View full text |Cite
|
Sign up to set email alerts
|

Reversible displacive transformation in MnTe polymorphic semiconductor

Abstract: Displacive transformation is a diffusionless transition through shearing and shuffling of atoms. Diffusionless displacive transition with modifications in physical properties can help manufacture fast semiconducting devices for applications such as data storage and switching. MnTe is known as a polymorphic compound. Here we show that a MnTe semiconductor film exhibits a reversible displacive transformation based on an atomic-plane shuffling mechanism, which results in large electrical and optical contrasts. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…In fact, utilizing the polymorphism for non-volatile memory application was reported recently for another telluride, MnTe. [24] Furthermore, the inverted structure may become a building block of currently unknown 2D vdW-bonded CdTe. The investigation of this issue is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, utilizing the polymorphism for non-volatile memory application was reported recently for another telluride, MnTe. [24] Furthermore, the inverted structure may become a building block of currently unknown 2D vdW-bonded CdTe. The investigation of this issue is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…As a nonlayered p-type semiconductor with a multiphase, α-MnTe has an ordered antiparallel magnetic moment with a Néel temperature of 307 K. It has been explored in memristor, magnetism, , thermoelectric, and photocatalytic applications and has shown superior properties like an above room temperature Néel temperature, good stability, high thermal conductivity, high carrier concentration, and reversible phase change. Since the controllable preparation of the 2D α-MnTe crystal is hard to achieve, most research has remained on the thin film until now, while the growth of the high quality crystal is limited to molecular beam epitaxy which is hard to industrialize.…”
Section: Introductionmentioning
confidence: 99%
“…MnTe is a typical polymorphism and stabilizes in hexagonal NiAs-type α-phase [nickeline (NC), Figure S1a] under normal atmospheric conditions, showing a phase change from α-phase to β-phase [wurtzite, Figure S1b], and then to γ-phase [zinc-blende, Figure S1c], and finally to δ-phase [salt-rock, Figure S1d] with the increase of temperature in the phase diagram. All of these MnTe phases exhibit antiferromagnetic (AFM) ground states. Recently, anisotropic magnetoresistance memory and magnetic anisotropy of α-MnTe have been reported to show the availability in AFM spintronic and memristive devices. , Thanks to the polymorphism, reversible resistive switching correlated to the reversible displacive transformation, which is between the α-phase (nickeline) and the β-phase (wurtzite), is found in MnTe and demonstrates a stronger competition in nonvolatile memory than in conventional phase-change Ge–Sb–Te materials . Interestingly, Balan et al reported the magnetic ordering transfer from the antiferromagnetic state to the paramagnetic one and the bandgap broadening from 1.3 to 2.1 eV when α-MnTe is confined to 2D form .…”
Section: Introductionmentioning
confidence: 99%